Penyuluhan Penanganan Luka dengan Aloe vera dan Kedaruratan Trauma Gigi kepada Ibu-Ibu PKK Kelurahan Cideng Jakarta Pusat - Roeslan, Moehamad Orliando; Poedjiastoeti, Wiwiek; Suwandi, Trijani; Zen, Yuniar; Wulansari, Selviana; Rizal, Muhammad Ihsan (JURNAL ABDIMAS KESEHATAN TERPADU, 2024)
Maintaining the dental and oral health of their children is greatly aided by mothers' awareness of dental emergencies. Dental emergencies might involve issues that need to be treated right once, like infections, chipped teeth, or damaged teeth. Aloe vera is a natural substance with remarkable healing qualities, which is why it is used in first aid for wounds. Aloe vera gel, which is readily extracted contains anti-inflammatory, antibacterial, and antioxidant substances that can help relieve pain, minimize swelling, and prevent infection. In Cideng Village, Gambir District, Central Jakarta, PKK women received counseling on handling wounds with aloe vera plants and dental trauma emergencies to increase their knowledge and abilities in dealing with dental trauma problems and wound healing with aloe vera. Faculty of Dentistry Universitas Trisakti Team from the dentistry education study program, the dentistry profession study program, and the master of dentistry study program completed this Community Service activity. Counseling and instructional media, including power point, videos, and posters, are used as part of community service projects. Through exams administered prior to counseling and compared with those administered following counseling, an increase in knowledge of tooth trauma crises and wound treatment using Aloe vera was gained in this activity. This counseling exercise is a crucial step in learning more about using Aloe vera to heal wounds from oral and dental injuries. It is necessary to keep taking a structural approach to the community. It is anticipated that social media counseling would expand its influence inside the community.